Educational System by Ovid Dekroli - Mashkina, Liudmyla (Pedagogical Discourse, 2014)
The article reveals the features of educational system of outstanding Belgian teacher Ovid Dekroli. The conceptual basis of his technology, particularly focused on a principle of anthropocentrism and the concentration of the educational program at the centers of interest have been elucidated. It shows the main topics of the author’s program of associated ideas written by Dekroli. Also it defines methodology of organization centers of interest. It focuses its attention on such elements as the observation, association and expression. In the article the features of the system and the principle of self-instructional materials in the form of educational games and card system tasks are defined. The attention is focused on the activities of the school «Hermitage», opened at the beginning of the XX century by O.Dekroli.